Almond Harvesting, Processing, and Microbial Flora - King, A. Douglas (1970)
This survey was set up on a statistical sampling plan to determine the microbial quality of almonds as they are received at the processing plant. The total aerobic bacterial count and yeast and mold count distribution were skewed by a few high counts compared with the majority of relatively low counts. Hard shell varieties of almonds had lower counts than did soft shell, and almonds with complete shells had lower counts than shelled almonds. Almonds harvested onto canvas had lower counts than those harvested by knocking onto the ground. Nuts with the least amounts of foreign material mixed into the sample had the lowest counts, as did nuts with the least amount of insect damage. Coliforms, Escherichia coli, and Streptococcus were isolated from the nuts, and their presence was correlated with soil contamination. When almonds are stored, the total plate count, the Streptococcus count, and the E. coli count after an initial drop remain nearly constant for more than 3 months. In addition to the indicator organisms, several genera of bacteria were isolated including Bacillus, Xanthomonas, Achromobacter, Pseudomonas, Micrococcus or Staphylococcus, and Brevibacterium.